Processes, Experiences, and Outcomes Associated With Accommodation and Nursing Students With Disabilities: A Scoping Review - Janes, Nadine; Fegan, Mary; Beekhoo, Zoraida; Gray, Mikaela (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
Background: More accessible nursing programs for a broader segment of society, including students with disabilities, will enhance diversity of thought in program curricula and representation among nurse graduates. Key to realizing these benefits is the ways in which nurse educators can best promote accessible and inclusive learning environments for nursing students with disabilities.Purpose: We completed a scoping review of published research reports, non-research publications, and dissertations related to accommodation and baccalaureate nursing students with disabilities. The review explored what is known from existing literature about the processes, experiences, and outcomes associated with classroom and clinical accommodation for nursing students with disabilities from the perspectives of learners and educators.Method: Online databases were used to identify literature that was written in English, published from 1990 to 2024, and focused on accommodation for nursing students with any visible or invisible disability within a nursing program leading to registered nurse status. Arksey and O’Malley’s (2005) methodological framework guided the selection of 84 publications, charting of the data, and summarizing results.Results: Accommodation processes are linked to disclosure, require collaboration, need to account for context, and must comply with legislation. The experience of accommodation for nursing students ranges from worrisome to supportive, while faculty experiences are similarly varied: feelings range from skepticism and internal struggle to acceptance and willingness. No standardized process and no universally accepted target outcome exist for the accommodation process. Tensions and uncertainties about how to best support nursing students with disabilities are ongoing.Conclusions: Intersectoral collaborative scholarly work is needed to advance practices for managing the complexities associated with the accommodation process in nursing education. Evidence is needed to ensure the process promotes equitable and inclusive experiences for nursing students with disabilities and supports nurse educators in managing their primary role through ample resources and professional development opportunities.